2017
DOI: 10.3174/ajnr.a5237
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of Disc in Young Patients with Low Back Pain and Stress Reaction in Lumbar Vertebrae

Abstract: Stressed discs exhibit a higher burden of nuclear and annular degeneration at baseline. These discs have a higher risk of progressive nuclear degeneration irrespective of improvement or worsening of stress-related bony changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…none supported a negative correlation. Outcomes were consistent throughout the clinical studies that showed a positive correlation, with all studies using MRI to diagnose bony stress and IVD degeneration (6,7,(18)(19)(20)(21) (7), which may suggest the importance of diagnosing early signs of bony stress even if the healing occurs in subsequent follow-up scans. Bony stress may also be a contributing factor to the non-speci c LBP, due to its association with IVD degeneration or due to the microtrabecular injury alone or both.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…none supported a negative correlation. Outcomes were consistent throughout the clinical studies that showed a positive correlation, with all studies using MRI to diagnose bony stress and IVD degeneration (6,7,(18)(19)(20)(21) (7), which may suggest the importance of diagnosing early signs of bony stress even if the healing occurs in subsequent follow-up scans. Bony stress may also be a contributing factor to the non-speci c LBP, due to its association with IVD degeneration or due to the microtrabecular injury alone or both.…”
Section: Discussionsupporting
confidence: 70%
“…The authors recognised early phases of bony stress on MRI and concluded that early imaging assessment may prevent a complete fracture non-union from occurring. Bony stress is thought to either alter load transmission throughout the IVD or occur secondary to the altered load distribution following IVD degeneration (7).…”
Section: Introductionmentioning
confidence: 99%
“…Finite Element (FE) modeling studies making use of imaging data from living human subjects or human cadaveric material Other discs in the lumbar spine, including the L5-S1 disc that normally experiences the greatest axial load, are spared from degeneration. 7 Image courtesy Sharma et al 2017.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Bony stress is thought to either alter load transmission throughout the IVD or occur secondary to the altered load distribution following IVD degeneration. 7 Whether IVD degeneration is a causative factor for discogenic LBP is unclear. [8][9][10] Discogenic LBP may arise from not only the structural failure of the IVD but also from nociceptive neurotransmitters, and neural and vascular ingrowth in the outer annulus fibrosus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation